Guidelines for music therapy practice in developmental health - Hintz, Michelle (Barcelona Publishers, 2013)
"This volume presents the current state of knowledge on the practice of music therapy with individuals of various ages and abilities who have developmental concerns, that is, individuals who need additional support, instruction, or therapy while pursuing developmental growth, learning, and skill acquisition. Included are chapters on early intervention, autism, Rett syndrome, developmental speech and language disorder, attentional deficits, learning disabilities, behavioral problems, hearing loss, visual impairment, mild to moderate intellectual disability, severe to profound developmental disabilities, physical disabilities, and severe and multiple disabilities. Practical guidelines are provided for implementing receptive, improvisational, re-creative, and compositional methods of music therapy with each client group. The guidelines are based on the clinical expertise and experience of the authors, and a comprehensive and critical review of available literature."--Publisher's website